ANALISIS PENGELOLAAN ADMINISTRASI KEUANGAN RUMAH TANGGA PETANI CAPTIKUS STUDI DI DESA WATULINEY KABUPATEN MINAHASA TENGGARA - Gloria Kalow; Allen Manongko; Iwan Kandori (Literacy: Jurnal Pendidikan Ekonomi, 2024)
ABSTRACK< strong>< p> The purpose of this study was to determine the Financial Administration Management of Captikus Farmer Households Study in Watuliney Village Southeast Minahasa Regency this research method is a qualitative approach method Based on the description above Captikus farmers in Watuliney Village face challenges in increasing their household income Although the average income is around 3 600 000 million Rupiah per month there are still Captikus farmer households who experience low income due to constraints such as limited production scale or limited market access To increase the income of Captikus farmer households steps have been taken such as product quality development training selection of superior varieties and increasing market access through cooperation with financial institutions or cooperatives The government also provides support through agricultural development programs and socialization of business management skills < p> Keywords:< strong> financial administration management of captikus farmer households< p> nbsp;< p> ABSTRAK< strong>< p> Tujuan penelitian ini dilakukan adalah untuk mengetahui Manajemen Administrasi Keuangan Rumah Tangga Petani Captikus Studi di Desa Watuliney Kabupaten Minahasa Tenggara metode penelitian ini adalah metode pendekatan kualitatif Berdasarkan uraian di atas petani Captikus di Desa Watuliney menghadapi tantangan dalam meningkatkan pendapatan rumah tangganya Meskipun pendapatan rata rata sekitar 3 600 000 juta Rupiah per bulan masih ada rumah tangga petani Captikus yang mengalami pendapatan rendah karena kendala seperti skala produksi terbatas atau akses pasar terbatas Untuk meningkatkan pendapatan rumah tangga petani Captikus telah dilakukan langkah langkah seperti pelatihan pengembangan mutu produk pemilihan varietas unggul dan peningkatan akses pasar melalui kerja sama dengan lembaga keuangan atau koperasi Pemerintah juga memberikan dukungan melalui program pengembangan pertanian dan sosialisasi keterampilan manajemen usaha < p> Kata Kunci:< strong> manajemen administrasi keuangan rumah tangga petani captikus< p>